2020
DOI: 10.1111/odi.13475
|View full text |Cite
|
Sign up to set email alerts
|

Mouse parotid salivary gland organoids for the in vitro study of stem cell radiation response

Abstract: Hyposalivation-related xerostomia is a major problem for patients treated with radiotherapy for head and neck cancer. The damage induced by the co-irradiation of salivary glands (SGs) results in severe hyposalivation-related side effects, such as oral dryness, difficulty with normal oral functions, loss of taste, ulcerations, and an increased risk of developing dental caries and oral infections. Consequently, the quality of life of these patients is drastically diminished (Langendijk et al.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…While low dose hypersensitivity is not a new phenomenon [ 73 , 74 ], this was the first study to show the relevance of this phenomenon in stem/progenitor cells, with a potential clinical relevance. Furthermore, we have recently developed a protocol for the culturing of parotid salivary gland organoids and demonstrated that parotid gland stem cells display a similar radiosensitivity as those of submandibular salivary glands [ 75 ]. Importantly, as organoids are derived from stem/progenitor cell populations, they allow for the study of a more stem/progenitor specific response.…”
Section: Organoids and Regeneration Of Radiation-induced Damaged Tmentioning
confidence: 99%
“…While low dose hypersensitivity is not a new phenomenon [ 73 , 74 ], this was the first study to show the relevance of this phenomenon in stem/progenitor cells, with a potential clinical relevance. Furthermore, we have recently developed a protocol for the culturing of parotid salivary gland organoids and demonstrated that parotid gland stem cells display a similar radiosensitivity as those of submandibular salivary glands [ 75 ]. Importantly, as organoids are derived from stem/progenitor cell populations, they allow for the study of a more stem/progenitor specific response.…”
Section: Organoids and Regeneration Of Radiation-induced Damaged Tmentioning
confidence: 99%
“…Moreover, taste bud organoids have been used to explore the effects of radiation on taste buds, suggesting SIRT1 inhibitors can promote Lgr5 + taste bud stem cell survival and mitigate radiation-induced oral mucositis (Guo et al 2019). SG organoids have also made progress in mimicking radiation damage in studying the mechanism of stem cell response to radiation (Serrano Martinez et al 2020).…”
Section: Potential Applications Of Oral Organoidsmentioning
confidence: 99%
“…Such stem cell therapy is an attractive option for the long‐term treatment of hyposalivation related xerostomia induced by irradiation, but is in need of further study in animals and preliminary studies in human before it can evolve into a clinically applicable method. Future studies should also focus on a better understanding of the radiosensitivity of parotid and submandibular salivary gland tissue (Serrano Martinez et al., 2020).…”
Section: Figurementioning
confidence: 99%
“…Such stem cell therapy is an attractive option for the long-term treatment of hyposalivation related xerostomia induced by irradiation, but is in need of further study in animals and preliminary studies in human before it can evolve into a clinically applicable method. Future studies should also focus on a better understanding of the radiosensitivity of parotid and submandibular salivary gland tissue (Serrano Martinez et al, 2020).All these developments show the benefits for patients of a good cooperation between primary and secondary caregivers. The good cooperation also demonstrates what can be achieved if efforts are focused and put into practice.…”
mentioning
confidence: 97%